The impact of vocational training programs on social security beneficiaries in the society of the United Arab Emirates During the COVID-19 - Al-Raisi, Fatima Khamis; Alothman, Husein (Al-Adab Journal, 2022)
The study aimed to identify the impact of vocational training on beneficiaries of social security, from the point of view of those who are attached to vocational training programs of beneficiaries of social security in the UAE society, as the study sample consisted of 240 beneficiaries of social security at the level of the United Arab Emirates, and to achieve the objectives of the study The researcher used the descriptive approach to analyze the data of the study sample members. The data was analyzed and interpreted and statistically processed using the spss program, by means of a social survey using the questionnaire study tool to obtain quantitative data, while qualitative data was done using a personal interview with a group of officials of the Ministry of Development Society for data collection. The results of the study showed that there is a statistical significance between the demographic study variables (educational level, income, marital status) on the one hand and the dependent variable of the study, which is enrollment in vocational training programs and its impact on social security beneficiaries. The results of the analysis indicated the effectiveness of vocational training programs and their impact on the beneficiaries of social security according to the axes, which are (the axis of satisfaction with the training programs, the axis of learning, the axis of behavior, and the axis of training results) from the point of view of the beneficiaries of social security.The most important recommendations reached by the researcher were: Follow-up of the authorities concerned with launching exhibitions and festivals by a working team assigned by the Ministry of Community Development, to ensure that those enrolled in the vocational training programs receive the appropriate training in the corner to win customers and sell all products. Integrating people with modest income from social security into economic programs and projects with the aim of ensuring a regular monthly income within a high investment and professional environment. Enacting laws and legislations for beneficiaries of social security and training, so that the participant in the training programs obtains privileges that qualify him to enter the labor market. Designing the innovative Small Merchant platform, with the presence of community partnerships between government, private and local sector institutions in order to support innovative projects through which it qualifies to stand in front of the local market. Familiarization with the best Arab and international practices in the field of modern technologies in the world of vocational training. Focusing on the department and management of research and studies and urging them to conduct research and studies in the field of vocational training that have a role in serving and advancing society.